Effects of Emigration on Gender Norms in Countries of Origin - Leonid V. Azarnert; Slava Yakubenko (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper studies the effect of emigration on gender norms in countries of migrants' origin. We use an instrumental variable strategy that allows us to estimate a causal effect of emigration on gender inequality. Our findings suggest that emigration to countries with low (high) levels of gender inequality is associated with promotion of more (less) progressive gender norms. These effects are observed for a wide range of indicators and are robust to inclusion of a set of control variables. Moreover, countries with high levels of gender inequality benefit from this process disproportionately more. Based on the provided evidence we argue that this effect is channelled through “cultural remittances”.
Keywords: F22; F63; J16; 330; migration; gender; cultural remittances